Accumulation of phosphorus fractions and contamination potential in vineyard soils in the southern region of the state of Santa Catarina, Brazil Acúmulo de frações de fósforo e potencial contaminante em solos de vinhedos na região sul do estado de Santa Catarina, Brasil - Schmitt D.E. (2013)
In vineyards, if phosphate is applied both before planting and at intervals during growth without consideration of technical criteria, the soil P fractions may be increased and their proportions altered. This study was carried out to evaluate the accumulation of P fractions and the parameters of the adsorption isotherm in a sandy Typic Hapludalf soil in vineyards with a history of successive and excessive phosphate fertilization. In December 2010, two vineyards were selected, one 4 and the other 15 years old, in Urussanga, State of Santa Catarina (Brazil). Three trenches were dug in each area and soil was collected from the 0-5, 5-10 and 10-20 cm depth ranges. The soil samples were dried in a forced-air oven, sieved and subjected to chemical analyses, P chemical fractionation and P adsorption isotherms. Excessive phosphate fertilization, before and during cultivation, particularly in the older vineyard and, consequently, with a longer history of phosphate fertilization, increased the inorganic P concentrations to the depth of 20 cm, especially in labile fractions extracted by anion exchange resin and NaHCO3 in the non-labile fraction, as well as in the non-labile fraction extracted by 1.0 mol L-1 HCl. The application of phosphate fertilizers and the long cultivation period increased the P levels in the organic labile fraction extracted by 0.5 mol L-1 NaHCO3, and especially in the moderately labile fraction extracted by 0.1 and 0.5 mol L-1 NaOH. Phosphate fertilization of older vineyards, i.e., cultivated for 15 years, increased the amounts of P desorbed in water, indicating a risk of contamination of surface waters and groundwater. The phosphate fertilization before planting, without considering the results of soil analysis, and during cultivation, disregarding the results of soil analysis, leaf analysis and expected yield, led to a reduction in the maximum P adsorption capacity in the 0-5 cm layer of vineyard 2, indicating saturation of part of the reactive particle adsorption sites.